Storytelling-Based Cultural Heritage Engagement for Children at Historical Tourism Sites: A Literature Review for Creative Industry Development - Han Xu; Fithriyah Inda Nur Abida; Indarti Indarti (Journal of Creative Industries and Vocational Innovation, 2026)
Historical tourism sites contain cultural, architectural, symbolic, and social meanings that may be difficult for school-age children to interpret through factual explanation alone. This narrative literature review examines how storytelling can support heritage engagement among children aged approximately 6–12 years and how this engagement can inform creative-industry development. Fourteen academic and institutional sources published between 1990 and 2025 were purposively synthesized across five themes: heritage interpretation, child-centered learning, site-based experience, digital and transmedia storytelling, and creative-industry pathways. The reviewed literature indicates that oral, visual, performative, digital, and gamified storytelling can support imagination, emotional connection, inquiry, and cultural awareness when narratives are linked to authentic places and participatory activities. Potential creative outputs include educational tours, children’s publishing, animation, games, augmented and virtual reality, workshops, performances, and culturally grounded merchandise. The article proposes a five-stage framework connecting heritage resources, child-centered narrative design, site-based experience, creative production, and cultural engagement outcomes. Its contribution is to integrate educational, heritage, and creative-industry perspectives while emphasizing historical accuracy, community participation, child safeguarding, accessibility, intellectual property, and fair benefit sharing. Because the review is narrative and based on a limited purposive corpus, the framework requires further testing through site-specific empirical studies